2012
DOI: 10.1095/biolreprod.111.094938
|View full text |Cite
|
Sign up to set email alerts
|

Rhox13 Is Translated in Premeiotic Germ Cells in Male and Female Mice and Is Regulated by NANOS2 in the Male1

Abstract: Male and female germ cells enter meiosis in response to an extrinsic cue by retinoic acid (RA), but the pathways downstream of RA signaling that regulate early gametogenesis remain uncertain. We identified a novel reproductive homeobox gene, Rhox13, transcribed in the prenatal ovary and testis beginning on Embryonic Day (E) 13.5. Translation of RHOX13 also begins in female germ cells on E13.5 but is suppressed in male germ cells until Postnatal Day 3. Translation of RHOX13 coincides with initiation of RA signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 43 publications
3
20
0
Order By: Relevance
“…We ruled out Rhox3 and Rhox13 as likely to be involved, as they are expressed in later stage germ cells than SSCs (Geyer et al, 2012; Song et al, 2015). Likewise, Rhox11 and Rhox12 are also unlikely to be responsible, as their postnatal expression pattern is consistent with primary expression in spermatids (Maclean et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…We ruled out Rhox3 and Rhox13 as likely to be involved, as they are expressed in later stage germ cells than SSCs (Geyer et al, 2012; Song et al, 2015). Likewise, Rhox11 and Rhox12 are also unlikely to be responsible, as their postnatal expression pattern is consistent with primary expression in spermatids (Maclean et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…This would not be entirely surprising, as the translation of many transcripts has been shown to be subject to regulation at different points of development in both male and female germ cells (Hecht 1998). Indeed, recently it has been reported that a member of Rhox gene cluster, Rhox13, is translationally repressed by the RNAbinding protein, NANOS2, in gonocytes and early spermatogonia (Geyer et al 2011). However, unlike RHOX13, RHOX10 is not translationally repressed in gonocytes but instead is highly expressed in these cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In the male, it is transcribed solely in germ cells throughout testis development, and mRNAs are detectable from E12.5 through adulthood (Geyer and Eddy 2008, Geyer, et al 2012). However, RHOX13 protein is only readily detectable in spermatogonia and preleptotene spermatocytes, is decreased dramatically in leptotene spermatocytes, and is undetectable in pachytene spermatocytes and spermatids (despite both cell types containing abundant Rhox13 mRNA) (Geyer and Eddy 2008, Geyer, et al 2012). To test the hypothesis that RHOX13 plays an essential role in male germ cell development, we took a reverse genetics approach to disrupt the Rhox13 gene.…”
Section: Resultsmentioning
confidence: 99%
“…However, RHOX13 protein is only readily detectable in spermatogonia and preleptotene spermatocytes. We found that Rhox13 mRNAs are repressed in prospermatogonia through a direct interaction with the RNA binding protein NANOS2, and this repression is apparently alleviated in response to RA (Chappell, et al 2013, Geyer, et al 2012). This translational control in the testis results in a protein expression pattern for RHOX13 that is remarkably similar to that in the female (oogonia/spermatogonia and preleptotene oocytes/spermatocytes), although they seem to be determined by distinct mechanisms.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation